2020
DOI: 10.3389/fbioe.2020.00406
|View full text |Cite
|
Sign up to set email alerts
|

Aged Tendon Stem/Progenitor Cells Are Less Competent to Form 3D Tendon Organoids Due to Cell Autonomous and Matrix Production Deficits

Abstract: Tendons are dense connective tissues, which are critical for the integrity and function of our musculoskeletal system. During tendon aging and degeneration, tendon stem/progenitor cells (TSPCs) experience profound phenotypic changes with declined cellular functions that can be linked to the known increase in complications during tendon healing process in elderly patients. Tissue engineering is a promising approach for achieving a complete recovery of injured tendons. However, use of autologous cells from aged … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 54 publications
2
25
0
Order By: Relevance
“…Additionally, downregulation of nuclear regulator CITED2 and Aquaporin 1(AQP1) are also reported to be correlated with TSPCs aging ( Hu et al, 2017 ; Chen et al, 2020 ). Functionally incompetent aged TSPCs will assemble into a less cell-populated, poorly organized and biomechanically inferior three-dimensional tendon organoids ( Yan et al, 2020 ). With advancing age, osteogenic differentiation potential and BMP expression are enhanced in TSPCs, which consequently contribute to increased heterotopic ossification in tendons ( Dai et al, 2020 ).…”
Section: Tspcs In Tendon Biologymentioning
confidence: 99%
“…Additionally, downregulation of nuclear regulator CITED2 and Aquaporin 1(AQP1) are also reported to be correlated with TSPCs aging ( Hu et al, 2017 ; Chen et al, 2020 ). Functionally incompetent aged TSPCs will assemble into a less cell-populated, poorly organized and biomechanically inferior three-dimensional tendon organoids ( Yan et al, 2020 ). With advancing age, osteogenic differentiation potential and BMP expression are enhanced in TSPCs, which consequently contribute to increased heterotopic ossification in tendons ( Dai et al, 2020 ).…”
Section: Tspcs In Tendon Biologymentioning
confidence: 99%
“…Alternatively, selfassembly models such as pellet and cell sheet cultures have gained a lot of interest, because they parallel the natural tissue formation process and secure native cell-to-cell and cell-to-matrix interactions, which initiate the appropriate and inherent cell signalling cascades of the used cell types (Yan et al, 2018). Previous studies have shown that mesenchymederived stem/progenitor cells, subjected to pellet and cell sheet culture protocols, were able to produce tenogenic (Hsieh et al, 2018;Yan et al, 2020) and chondrogenic scaffold-free tissues (Pattappa et al, 2019a;Pattappa et al, 2019b).…”
Section: Col14a1mentioning
confidence: 99%
“…In this study, the PDL tissue-forming ability of DFCs was investigated, in comparison to the previously established and characterised PDL-hTERT cell line (Docheva et al, 2010), by using a novel self-assembly 3D organoid model for tenogensis/ ligamentogensis (Hsieh et al, 2018;Yan et al, 2020) and by carrying out detailed histomorphometric, quantitative PCR and protein analyses.…”
Section: Col14a1mentioning
confidence: 99%
See 1 more Smart Citation
“…Our previous study proved that human TSPCs have great potential to form well-aligned and collagen-rich cell sheets [ 95 ]. Moreover, our further research revealed that aged/degenerative TSPCs exhibit defective cell sheets compared to young/healthy TSPCs [ 96 ], demonstrating that the cell sheet model is suitable to mimic in vitro tenogenic differentiation process as well as to investigate pathomechanisms involved in tendon aging. Hence, it will be of great interest to perform a follow up study with the aim to subject DFs to the tendon cell sheet protocol.…”
Section: In Vitro Studiesmentioning
confidence: 99%